Lessons as the main form of organization of educational work - Batashov Innatullo Qo’ng’irovich (Zien Journals, 2022)
The article is dedicated to him in order to effectively organize the lessons in the educational process requirements, types of lessons according to the didactic purpose, scientific significance of the purpose, tasks and stages of the lesson
Keywords: lesson; method; purpose; task